Differences and changes in the physical characteristics of professional and amateur rugby union players - Smart, D. J.; Hopkins, W. G.; Gill, N. D. (The Journal of Strength and Conditioning Research, 2013)
Numerous studies have highlighted differences between playing levels and positions in rugby union; however, few studies have investigated longitudinal progressions of body composition and physical performance. Between-player differences and within-player changes in body composition, strength, power, speed, and repeated sprint ability, from 1,161 New Zealand rugby union players from 2004 to 2007, were estimated using a mixed modeling procedure. Props had the highest mass, percent body fat, strength, and slowest speed times compared with the other positions, whereas outside backs had the fastest speed time and lowest percent body fat. For most measures, there were small-to-moderate differences (range, 1.1-14%) between players selected and not selected for provincial teams and small-to-large differences (range, 1.8-15%) between provincial and Super Rugby (professional) players. The faster 20-m sprint times in international compared with Super Rugby players was small in magnitude for both the forwards (1.9%) and backs (2.2%). The average annual improvements were small to moderate for strength (range, 2.1-15%) and small for repeated sprint ability within the lower playing levels (~1.5%). Small increases occurred in lower body strength (~7.0%) as players moved from Super Rugby to provincial competition. Small decreases in sprint time (~1.6%) and small increases in strength (~6.3%) occurred as players moved from Super Rugby to midyear international competition. The differences between levels in performance provide level-specific characteristics from Super Rugby and below, but international players may be selected because of greater skill and experience. Changes in physical performance between competitions may be a result of reduced training loads because of regular high-intensity matches and greater travel involved in the Super Rugby competition.